2022
DOI: 10.1167/iovs.63.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Molecular Signature of Human Hyalocytes in Relation to Other Innate Immune Cell Populations

Abstract: Purpose Hyalocytes are the tissue-resident innate immune cell population of the vitreous body with important functions in health and vitreoretinal disease. The purpose of this study is to gain new insights into the biology and function of human hyalocytes in comparison to other innate immune cells. Methods The present study applies fluorescence-activated cell sorting and RNA sequencing to compare the transcriptional profiles of human hyalocytes, retinal microglia (rMG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…There are two kinds of specific resident macrophages on the normal inner limiting membrane: hyalocyte and microglia ( 15 ). A previous study revealed distinct differences between hyalocytes and monocytes, but a high degree of similarity was observed between these two cells ( 26 ). Although we could not differentiate microglia and hyalocytes based on label-free en face OCT, cumulative evidence has shown that both cells undergo proliferation and activation in neuroinflammation ( 12 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 86%
“…There are two kinds of specific resident macrophages on the normal inner limiting membrane: hyalocyte and microglia ( 15 ). A previous study revealed distinct differences between hyalocytes and monocytes, but a high degree of similarity was observed between these two cells ( 26 ). Although we could not differentiate microglia and hyalocytes based on label-free en face OCT, cumulative evidence has shown that both cells undergo proliferation and activation in neuroinflammation ( 12 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 86%
“…Transcriptional profiling of human hyalocytes finds that these cells present antigens and participate in immune privilege of the vitreous [ 35 ]. Compared to retinal microglia, human hyalocytes were enriched for angiogenesis and chemotaxis gene ontology terms, suggesting a potential role for hyalocytes in the inflammatory component of DR and RVO [ 36 ]. In addition, both diseases can cause vision loss from tractional retinal detachments that form as neovascular membranes contract at the vitreoretinal interface.…”
Section: Discussionmentioning
confidence: 99%
“…Vitreal hyalocytes are another potential MLC identity. Hyalocytes are resident macrophages of the vitreous that present antigens, participate in immune privilege, and express pro-angiogenic and pro-chemotactic transcriptional profiles [ 22 , 23 ]. Thus, MLCs could include vitreal hyalocytes promoting angiogenesis and immune cell infiltration in DME eyes.…”
Section: Discussionmentioning
confidence: 99%